PESSIMISM AND INTELLECTUAL NETWORKS IN PUEBLO ENFERMO (1909) BY ALCIDES AGUEDAS (1879-1946) - Diniz, Cláudio (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes the work Pueblo enfermo (1909), by Bolivian writer Alcides Arguedas, from the perspective of the history of ideas, with an emphasis on the intellectual networks to which the author was linked and on pessimism as a structuring mark of his sociological analysis of Bolivia. The work is examined in the context of national defeats (War of the Pacific and Chaco War), racist ideas and regenerationism, highlighting the way in which Arguedas constructed an image of the country as morally and racially degenerate. The article highlights the adoption of categories such as “race”, “environment” and “historical moment”, inherited from positivism and the French tradition (Taine, Gobineau), in the constitution of a pathological diagnosis of the nation. The study also explores Arguedas’ personal diary as a source for understanding the process of creation, reception and reformulation of the work, especially in the third edition of 1937, which includes a chapter on the rise of the Bolivian military. Arguedas's affiliation with Arielism, Spanish regenerationism, and Latin American essayist networks from the early 20th century highlights how his pessimistic critique was part of a transnational circuit of circulation of ideas. Although imbued with scientific racism, the work proposes a therapeutic approach based on culture and education, expressing the tension between degeneration and regeneration in Latin American social thought at the time.